Dielectric Characterization of Breast Cancer Cells using Split-Rectangular Ring Resonator Sensor - Jabire, Adamu Halilu; Saminu, Sani; Adamu, Muhammed Jajere; Mohammed, Abubakar Saddiq; Aminu, Sha'awanatu; Sadiq, Abubakar Muhammad (Buletin Ilmiah Sarjana Teknik Elektro, 2025)
Exploring a universal method to enhance the performance of metamaterials by quantifying the impact of gap capacitance is an intriguing topic for many researchers. However, achieving this through conventional methods is extremely challenging. In this paper, we present a microwave sensor designed to characterize cancerous cells based on their electrical properties. The proposed design features a split rectangular ring resonator placed on a flame-retardant four (FR-4) substrate. The sensor aims to achieve high sensitivity and quality factors through the unique characteristics of the metamaterial structure in the GHz frequency range. Through simulations and experimental measurements, we demonstrate the sensor's effective capabilities in detecting cancer. The high sensitivity for both simulation and measurement, is estimated at 10 %. The simulations and validation confirm that this biosensor exhibits significant frequency shifts and high sensitivity. Our proposed configurations highlight the microwave sensor's potential for detecting six different breast cancer cell types: HSS-2, HS578-T_nm, MCF-2, MCF-10A_nm, T-47D, and T-47D_nm. Based on the existing literatures, the sensitivity of the proposed sensor is determined to be greater.